Mental Health and Other Factors Associated with COVID-19 Vaccination Intention toward Children of Military Parents in Lambayeque, Peru - Mario J. Valladares-Garrido; Aldo Alvarez-Risco; Annel B. Rojas-Alvarado; Cinthia Karina Picón-Reátegui; Franccesca Dawson Aguila; Shyla Del-Aguila-Arcentales; Neal M. Davies; Virgilio E. Failoc-Rojas; César Johan Pereira-Victorio; Danai Valladares Garrido; Víctor J. Vera-Ponce; Jaime A. Yáñez (The Scientific World Journal)
There is evidence that vaccine acceptability is strongly associated with mental health. However, no studies assessing intention to vaccinate (ITV) intention toward children of military parents have been documented. The current research aimed to establish the prevalence and factors of ITV children against COVID-19 in military parents in Lambayeque-Peru, 2021. Analysis was conducted with the dependent variable ITV children reported by military parents. The independent variables were history of mental health, searching for mental health support, food insecurity, resilience, anxiety, depression, burnout, posttraumatic stress, and suicidal risk. Prevalence ratios and 95% confidence intervals were estimated. Of 201 military personnel evaluated, 92.5% were male, 82.5% were of the Catholic faith, and the median age was 40.9% of respondents reported seeking mental health help during the COVID-19 pandemic. It was reported anxiety (20.3%), depression (6.5%), and posttraumatic stress disorder (6.5%). Most reported ITV in children against COVID-19 (93%). In the multiple models, we found that Catholics had a 23% higher prevalence of ITV in the children where PR = prevalence ratios and CI = confidence intervals (PR = 1.23; 95% CI: 1.01–1.50). Likewise, seeking mental health support increased the prevalence of ITV by 8% (PR = 1.08; 95% CI: 1.00–1.15). Seeking mental health support and belonging to the Catholic faith had a higher ITV of children of Peruvian military personnel. Finding mental health support, experiencing burnout syndrome, having a relative who suffers from mental health problems, and being part of the Catholic religion were associated with a higher willingness to immunize the children of Peruvian military members.